The influential healthcare factors in medical waste management in a Serbian hospital setting - Jovanović, Verica (PONS - medicinski časopis, 2017)
Introduction: Proper Medical Waste Management was introduced in the Republic of Serbia in 2009 with the support of the European Union. Since then, the amounts of waste treated, prior to landfill, have steadily increased and more and more healthcare institutions adopted medical waste management systems. In parallel large numbers of healthcare workers were trained in proper HCWM. This study quantifies the progress made. Objectives: The aim of the study was to analyze different factors of hospital healthcare in Serbia. Specific objectives of the study were: 1. To assess correlations between said factors and medical waste management focused on hazardous medical waste streams in the study population. 2. To suggest appropriate recommendations regarding influencing factors of medical waste management in study population. Methods: The research was carried out as a cross-sectional study of a representative secondary and tertiary level hospital sample in the public domain, in November 2014. A special questionnaire was developed and employed for the survey, based on the UN–WHO guidelines for the rapid assessment of medical waste management in a hospital setting, filled in by medical waste managers from the selected hospitals. Results: By using Mann Whitney U-test statistically significant difference was found between secondary level of healthcare (MD=23.393, N=43) and tertiary level hospitals (MD=40000, N=17) (U=198, p=0.006) concerning generated quantities of medical waste. Statistically significant difference was found with regards to the level of healthcare, when it comes to medical waste generation (U=198, p=0.006), pathological waste generation (U=132, p=0.000), and pharmaceutical waste generation (U=221, p=0.018) in a healthcare setting. Tertiary healthcare level hospitals produce statistically significantly bigger quantity of hazardous medical waste in all pertinent categories (U=198, p=0,006). There is a direct and strong correlation between the total number of beds, hospital days, healthcare services provided and staff members trained in the area of medical waste management, identified as the main factors that impact the management of hazardous medical waste. Conclusion: The success rate of medical waste management practice varies, depending on the type of the institution at hand, its level of healthcare, as well as the nature and severity of the medical waste. Continual improvement of the mechanics of medical waste management is among the most prioritised goals of hospitals, as a way of bettering the quality of healthcare in general. Keywords: Medical waste; medical waste management; health care services; influential factors